The thief of Lanwyn Manor - Ladd, Sarah E (Thomas Nelson, 2020)
"Perfect for fans of Poldark, Sarah E. Ladd's latest Regency romance, The Thief of Lanwyn Manor, explores Cornwall, England, and the secrets within one of its historic manor houses"--